1989
DOI: 10.1017/s0266467400003680
|View full text |Cite
|
Sign up to set email alerts
|

Patterns of seed rain at the edge of a tropical Queensland rain forest

Abstract: Both vertebrate- and wind-dispersed seeds moved farther from rain forest into old field than from old field into forest. Vertebrate-dispersed seeds from the rain forest moved farther into the field than wind-dispersed seeds, but seeds of both types moved similar distances from field into forest.Habitat structure affected seed deposition patterns in the field, where shrubs provided perches for flying vertebrates. Vertebrate-dispersed seed deposition was significantly greater, and deposition of plumed, wind-disp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
76
2
8

Year Published

1992
1992
2011
2011

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 120 publications
(102 citation statements)
references
References 15 publications
7
76
2
8
Order By: Relevance
“…In a reserve covered by patches of cerrado sensu stricto and campo cerrado, intensively invaded by alien grasses, graminoid species do not seem to be affected by the distance of the border (Pivello et al, 1999). Seed dispersal should be influenced by the permeability of the vegetation (physical obstruction imposed by the architecture of plants) to the flux of seeds (Willson and Crome, 1989). Wind-dispersed seeds crossing a thinned vegetation edge disperse farther into the fragment interior (Cadenasso and Pickett, 2001).…”
Section: Discussionmentioning
confidence: 99%
“…In a reserve covered by patches of cerrado sensu stricto and campo cerrado, intensively invaded by alien grasses, graminoid species do not seem to be affected by the distance of the border (Pivello et al, 1999). Seed dispersal should be influenced by the permeability of the vegetation (physical obstruction imposed by the architecture of plants) to the flux of seeds (Willson and Crome, 1989). Wind-dispersed seeds crossing a thinned vegetation edge disperse farther into the fragment interior (Cadenasso and Pickett, 2001).…”
Section: Discussionmentioning
confidence: 99%
“…The effect of distance from the forest may vary with species' dispersal mechanisms and site factors; for example in a temperate system Holl & Crone (2004) found that only winddispersed species are affected by distance from the forest, whereas animal-dispersed species are more influenced by site factors. Similarly, in a tropical context distance from the forest has little effect on animal-dispersed seed rain at some sites adjacent to forest that are near isolated trees and shrubs (Guevara, Purata & Van der Maarel 1986;Willson & Crome 1989). These results contrast with findings at other tropical locations that seedling density decreases sharply with increasing distance from the forest edge (Aide & Cavelier 1994), as does seed rain density (Nepstad, Uhl & Serrão 1990;Gorchov et al 1993;Aide & Cavelier 1994;Holl 1999;Wijdeven & Kuzee 2000) and frugivore abundance (Cardosa da .…”
Section: mentioning
confidence: 92%
“…Todo este processo acaba sendo um fator selecionador das comunidades capazes de se instalar e utilizar as bordas como área de desenvolvimento, devido às adaptações necessárias para as espécies habitarem com sucesso esses ambientes ecotonais (Willson & Crome 1989;Malcolm 1994). A distribuição das espécies num ambiente reflete o nível de adaptabilidade frente às diversas pressões seletivas, uma vez que devem existir condições essenciais à sobrevivência para que ocorra a ocupação e a colonização de determinado local (Ridley 2006;Rizzini 1997).…”
Section: Introductionunclassified